An attempt of reconstruction of burial rite according to the materials from the tomb No. 608 of Karashamb - Melikyan, Varduhi (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
As a result of recent excavations at the necropolis of Karashamb new data have emerged concerning burial rite, the reconstruction of which enables to use them with purpose of clarification of various aspects of social life in early societies, among which - social behaviour, cultural belonging, chronology, social structure, world-outlook, cult and religion, etc.